NOAA/WDS Paleoclimatology - Mackenzie Delta, NW Canada 750 Year Summer Temperature Reconstruction - Porter, T.J.; Pisaric, M.F.J.; Kokelj, S.; deMontigny, P. (NOAA National Centers for Environmental Information, 2016)
This archived Paleoclimatology Study is available from the NOAA National Centers for Environmental Information (NCEI), under the World Data Service (WDS) for Paleoclimatology. The associated NCEI study type is Climate Reconstruction. The data include parameters of climate reconstructions|tree ring with a geographic location of Northwest Territories, Canada. The time period coverage is from 705 to -57 in calendar years before present (BP). See metadata information for parameter and study location details. Please cite this study when using the data.